If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 10 = 15 + -9 Reorder the terms: 10 + 8x = 15 + -9 Combine like terms: 15 + -9 = 6 10 + 8x = 6 Solving 10 + 8x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 8x = 6 + -10 Combine like terms: 10 + -10 = 0 0 + 8x = 6 + -10 8x = 6 + -10 Combine like terms: 6 + -10 = -4 8x = -4 Divide each side by '8'. x = -0.5 Simplifying x = -0.5
| P^2=8p | | 3lnx-5lnx=3 | | 5+7x+3x=75 | | 4g-20=9g | | x^4-10x^3+35x^2-65x+48=0 | | -8d-9=-7d | | -6x-8=22-4x | | 16n^2=64 | | -5(1-5n)+3=25-2n | | f(x)=2ln(x+1) | | -5-6x+2x=-29 | | .4x-.5(2x+7)=-.7(X+4) | | 9+5x-3x=14+5 | | 7(x+2)=3x-3+4x | | 4x+3+6x+6=52 | | -5+6x-12y=24 | | 2x^2-13=10x | | -t=-2-10 | | inx+in(x-6)=in(2x) | | 8x-58=2*2+34 | | 8=8(1-6k) | | 1h=1 | | 6x+4x+6+4=38 | | -9+6w=5w | | a^2+1=29 | | 3(5y+2)-y=u+8 | | -92=4(-7x-2) | | 5x+55=9x-9 | | 2(3a+9)=20 | | 26p-4-11p=15p+6 | | 8x-4=4x+44 | | -6(4x+7)=78 |